PENGARUH CYBER PUBLIC RELATIONS TERHADAP CITRA RADIO REPUBLIK INDONESIA PROGRAMA 2 PEKANBARU - Vega Aisyah Alifia Khan Biryanto; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Radio Republik Indonesia (RRI) Programa 2 Pekanbaru is a public broadcasting institution that has an important role in controlling the social. That is the reason wht its presence needs to be maintained in order to create the good quality of our nation’s generation. The era of good technology has provided various media that can support RRI Programa 2 Pekanbaru to create a positive image, one of them is about the adoption of cyber public relations strategy for all of their activities. This aims to build and maintain its image as a good public broadcasting institution. The target of RRI Programa 2 Pekanbaru its self reach the 19 tio 35 years age that categorized as the productive range. As the majority of social media’s user, the cyber public realtions will be easier to catch the public attention. This research is used a quantitative method, with a simple linear regression analysis technique that looking for the impacts or the influence of cyber public relations towards the image of RRI Programa 2 Pekanbaru. The result show that cyber public relations has a positive and significant effect and impacts 73,6% to the image. This proof just indicates that the transition from a conventional era to the digital, brings the improvement for RRI Programa 2 Pekanbaru to attract more audience based on their image.